Fundamental movement skills in relation to weekday and weekend physical activity in preschool children. Issue 6 (November 2015) - Foweather, Lawrence; Knowles, Zoe; Ridgers, Nicola D.; O'Dwyer, Mareesa V.; Foulkes, Jonathan D.; Stratton, Gareth
Abstract: Objectives: To examine associations between fundamental movement skills and weekday and weekend physical activity among preschool children living in deprived communities. Design: Cross-sectional observation study. Methods: Six locomotor skills and 6 object-control skills were video-assessed using The Children's Activity and Movement in Preschool Study Motor Skills Protocol. Physical activity was measured via hip-mounted accelerometry. A total of 99 children (53% boys) aged 3–5 years ( M 4.6, SD 0.5) completed all assessments. Multilevel mixed regression models were used to examine associations between fundamental movement skills and physical activity. Models were adjusted for clustering, age, sex, standardised body mass index and accelerometer wear time. Results: Boys were more active than girls and had higher object-control skill competency. Total skill score was positively associated with weekend moderate-to-vigorous physical activity ( p  = 0.034) but not weekday physical activity categories ( p  > 0.05). When subdomains of skills were examined, object-control skills was positively associated with light physical activity on weekdays ( p  = 0.008) and with light ( p  = 0.033), moderate-to-vigorous ( p  = 0.028) and light- and moderate-to-vigorous ( p  = 0.008) physical activity at weekends. Locomotor skill competency was positively associated with moderate-to-vigorous physical activity on weekdays ( p  = 0.016) and light physical activity during the weekend ( p  = 0.035). Conclusions: The findings suggest that developing competence in both locomotor and object-control skills may be an important element in promoting an active lifestyle in young children during weekdays and at weekends.